2023
DOI: 10.48550/arxiv.2303.15662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ChatGPT4PCG Competition: Character-like Level Generation for Science Birds

Abstract: This paper presents the first ChatGPT4PCG Competition at the 2023 IEEE Conference on Games. The objective of this competition is for participants to create effective prompts for ChatGPT-enabling it to generate Science Birds levels with high stability and character-like qualities-fully using their creativity as well as prompt engineering skills. ChatGPT is a conversational agent developed by OpenAI. Science Birds is selected as the competition platform because designing an Angry Birds-like level is not a trivia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…into the importance of prompt engineering, the development of frameworks and strategies for structuring prompts, and the evaluation of LLM performance on complex tasks. 5,6,[24][25][26][27][28][29] These studies highlight the significance of prompt engineering when working with models like GPT-4 and provide relevant context for using LLMs in advanced research, such as the present study on SRT. This work differs from these studies in that it specifically evaluates GPT-4, which is posited to possess emergent, foundational AGI behaviors.…”
Section: Related Workmentioning
confidence: 93%
“…into the importance of prompt engineering, the development of frameworks and strategies for structuring prompts, and the evaluation of LLM performance on complex tasks. 5,6,[24][25][26][27][28][29] These studies highlight the significance of prompt engineering when working with models like GPT-4 and provide relevant context for using LLMs in advanced research, such as the present study on SRT. This work differs from these studies in that it specifically evaluates GPT-4, which is posited to possess emergent, foundational AGI behaviors.…”
Section: Related Workmentioning
confidence: 93%
“…White et al, Sorensen et into the importance of prompt engineering, the development of frameworks and strategies for structuring prompts, and the evaluation of LLM performance on complex tasks. [5,6,[24][25][26][27][28][29] Their works provide a pivotal scaffold for advanced research applications of LLMs, as demonstrated in the current study.…”
Section: Related Workmentioning
confidence: 96%
“…Numerous research studies have explored various methods for creating game levels in Angry Birds. Prior investigations have tackled this problem from diverse angles, proposing solutions to intriguing challenges, such as generating stable structures within the physical environment , dynamically adjusting the game levels' difficulty (Stephenson and Renz 2019), creating block structures based on hand-drawn sketches (Stephenson et al 2021), generating deceptive levels to deceive AI agents (Gamage et al 2021a), generating novel scenarios for physics environments (Gamage et al 2023(Gamage et al , 2021b and, most recently, using prompt engineering to create prompts for level generation (Taveekitworachai et al 2023). None of the previous studies has treated the level generation for Angry Birds as a task generation problem that incorporates the physical interactions between the game objects.…”
Section: Physics Based Puzzle Gamesmentioning
confidence: 99%